Search for hidden-charm tetraquark with strangeness in *Supported in part by National Key R&D Program of China (Grant Nos. 2020YFA0406400, 2020YFA0406300); National Natural Science Foundation of China (NSFC) (Grant Nos. 11635010, 11735014, 11805086, 11835012, 11935015, 11935016, 11935018, 11961141012, 12022510, 12025502, 12035009, 12035013, 12192260, 12192261, 12192262, 12192263, 12192264, 12192265); the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program; Joint Large-Scale Scientific Facility Funds of the NSFC and CAS(Grant No. U1832207); the CAS Center for Excellence in Particle Physics (CCEPP); 100 Talents Program of CAS; Fundamental Research Funds for the Central Universities, Lanzhou University, University of Chinese Academy of Sciences; The Institute of Nuclear and Particle Physics (INPAC) and Shanghai Key Laboratory for Particle Physics and Cosmology; ERC (Grant No. 758462); European Union's Horizon 2020 research and innovation programme under Marie Sklodowska-Curie grant agreement (Grant No. 894790) ; German Research Foundation DFG (Grant No. 443159800), Collaborative Research Center CRC 1044, GRK 2149; Istituto Nazionale di Fisica Nucleare, Italy; Ministry of Development of Turkey (Grant No. DPT2006K-120470); National Science and Technology fund; National Science Research and Innovation Fund (NSRF) via the Program Management Unit for Human Resources & Institutional Development, Research and Innovation (Grant No. B16F640076); Olle Engkvist Foundation (Grant No. 200-0605); STFC (United Kingdom); Suranaree University of Technology (SUT), Thailand Science Research and Innovation (TSRI), and National Science Research and Innovation Fund (NSRF) (Grant No. 160355); The Royal Society, UK (Grant Nos. DH140054, DH160214); The Swedish Research Council; U. S. Department of Energy (Grant No. DE-FG02-05ER41374). (1st March 2023) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Adlarson, P.; Albrecht, M.; Aliberti, R.; Amoroso, A.; An 安, M. R. 美儒; An 安, Q. 琪; Bai 白, Y. 羽; Bakina, O.; Baldini Ferroli, R.; Balossino, I.; et al.
Abstract: We report a search for a heavier partner of the recently observed state, denoted as, in the process, based on collision data collected at the center-of-mass energies of, 4.682 and 4.699 GeV with the BESIII detector. The is of interest as it is expected to be a candidate for a hidden-charm and open-strange tetraquark. A partial-reconstruction technique is used to isolate recoil-mass spectra, which are probed for a potential contribution from ( ). We find an excess of ( ) candidates with a significance of, after considering systematic uncertainties, at a mass of . As the data set is limited in size, the upper limits are evaluated at the 90% confidence level on the product of the Born cross sections ( ) and the branching fraction ( ) of, under different assumptions of the mass from 4.120 to 4.140 MeV and of the width from 10 to 50 MeV at the three center-of-mass energies. The upper limits of are found to be at the level of pb at each energy. Larger data samples are needed to confirm the state and clarify its nature in the coming years.